2018
DOI: 10.3390/ijerph15091902
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Growth on Dust-Loaded Filtering Materials Used for the Protection of Respiratory Tract as a Factor Affecting Filtration Efficiency

Abstract: This work aims at understanding the effects of various dust-loading conditions and the type of nonwovens used in the construction of FFRs on the safe use of those protective devices in situations of exposure to biological agents. The survival of microorganisms (Escherichia coli, Candida albicans, and Aspergillus niger) in dust-loaded polypropylene nonwovens (melt-blown, spun-bonded, and needle-punched) was experimentally determined using microbiological quantitative method (AATCC TM 100-2004). Scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Translating the results of laboratory tests into the actual use, it should be stated that the more effective the FFRs are, the more microorganisms will accumulate inside them. Their growth can constitute a danger to the user [21,22,23]. Therefore, the use of standard FFRs throughout the working shift for protection against biological agents does not guarantee a sufficient protection of the user.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Translating the results of laboratory tests into the actual use, it should be stated that the more effective the FFRs are, the more microorganisms will accumulate inside them. Their growth can constitute a danger to the user [21,22,23]. Therefore, the use of standard FFRs throughout the working shift for protection against biological agents does not guarantee a sufficient protection of the user.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, despite numerous research and development studies aimed at conferring biocidal properties to filtering nonwovens [4,5,6,7,8,9,10,11,12,13,14,15], there are no FFRs on the market that guarantee restricted growth of microorganisms accumulated on the filtering material during use. At the same time, many studies [16,17,18,19,20,21,22,23] confirmed that during prolonged FFR use against bioaerosols, bacterial numbers may increase, and biofilms may form on the filtering nonwoven, which may become a potential threat for the user. Likewise, it was found that during influenza A (H1N1) pandemics, viruses and microorganisms survived on the filtering material of SRs used by the personnel for several hours to several days [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes are common among the bacterial populations in the human microbiome and are not likely to be eradicated, even in the absence of antibiotic selection [74]. Therefore, it is important to use personal protective equipment (respiratory protection masks, footwear, protective clothing, and gloves), effective and efficient ventilation, as well as limiting the employees' working time in these conditions [75]. Although, there is a lack of BAQ standards in Polish legislation, the key problem is keeping a high standard of air quality, and we hope that the results of this campaign may indicate the usefulness of periodic microbiological environmental monitoring to verify the quality of the air and to establish possible technologically achievable guide levels of contamination for a specific work environment.…”
Section: Discussionmentioning
confidence: 99%
“…The AATCC 100-1998 “Antimicrobial Finishes of Textile Materials” quantitative method was used to assess microorganism survival on filtering nonwovens. Microbial inocula were prepared according to a previously described method [37]. The inoculation suspension density at the level of 1.9 × 10 6 CFU/mL for B. subtilis , 7.5 × 10 8 CFU/mL for E. coli , 8.7 × 10 9 CFU/mL for S. aureus , 1.0 × 10 8 CFU/mL for C. albicans and 3.8 × 10 6 CFU/mL for A. niger was determined using the culture method and Thom chamber.…”
Section: Methodsmentioning
confidence: 99%